The Influence of Community Empowerment Training for Inland Water Transport Ship Loaders on Students’ Knowledge and Skills - Amanda, Monica; Kartini, Sri; Sidharta, Driaskoro Budi; Triwahyuni, Siti Nurlaili; Febriansyah, Febriansyah; Komalasari, Yeti (Jurnal Pengabdian kepada Masyarakat (Indonesian Journal of Community Engagement), 2024)
The causes of shipping accidents, as identified by the KNKT investigation, included technical, weather, and human factors. As a result, community empowerment training was conducted in 2023 for loaders of inland waterway transport vessels Class I. This training aimed to enhance participants’ knowledge, insight, and skills regarding loading arrangements and stability testing of inland waterway vessels. The study employed a quantitative descriptive method using primary data from evaluations, including pretests and posttests administered to 30 training participants. The analysis technique utilized was the paired t-test. Results obtained through the Wilcoxon Matched Pair test indicated a significant difference between pretest and posttest scores, leading to the conclusion that participants’ knowledge improved after completing the training. The findings revealed that, out of 30 training participants, only 2 experienced a decrease in scores. Conversely, 28 participants showed positive results (positive rankings), indicating an increase in scores. The average pretest score was 73.67, which increased to an average posttest score of 92.50 following the training. These results were further supported by the significant difference shown in the paired t-test analysis. In conclusion, there was a significant improvement in participants’ knowledge after the training. It is recommended that the program be expanded to include more participants to ensure that the broader community, particularly ship operators, benefits from increased knowledge of shipping safety and proper ship loading practices.